Taping-induced cutaneous stimulation to the ankle tendons reduces minimum toe clearance variability. Issue 1 (January 2023) - Pathak, Prabhat; Ahn, Jooeun
Abstract: Large variability of minimum toe clearance (MTC) leads to a higher risk of tripping. Visual feedback-based gait training systems have been used to regulate MTC distribution, but these systems are expensive and bulky. Furthermore, the effect of such training lasts only for a short period of time. Considering the efficacy of elastic adhesive tape-induced cutaneous stimulation to the ankle tendons in improving proprioception and movement detection, we hypothesize that application of tapes to the ankle tendons as a practical method for modifying MTC distribution. To test this hypothesis, we recruited 13 young and healthy adults and instructed them to walk on a treadmill under four conditions: no taping, taping the tibialis anterior tendon, taping the Achilles tendon, and taping both tendons. We measured MTC distribution, lower limb joint angles and muscle activations of the tibialis anterior and gastrocnemius medialis, and compared these outcomes under the four conditions. The application of elastic adhesive tape to the ankle tendons had no significant effect on the average MTC height, but tapes applied to the Achilles tendon and both tendons significantly reduced MTC variability. Taping decreased the variability of some lower limb joint angles, but taping did not induce significant changes in the activation levels of the shank muscles. These results demonstrate that elastic adhesive tape applied to the shank can reduce MTC variability with minimal resistance, inertia and cumbersomeness. Highlights: Large variability of minimum toe clearance (MTC) increases the risk of tripping. Cutaneous stimulation can enhance proprioception and control of the foot. Elastic adhesive tape can provide cutaneous stimulation without discomfort. We demonstrated that taping ankle tendons actually reduces MTC variability.